The use of objective structured clinical examination in dental education- a narrative review - Mohammad Ramadan Rayyan (Frontiers Media S.A., 2024)
The Objective Structured Clinical Examination (OSCE) is a performance-based assessment intended to assess medical students' clinical competency in a simulated, standardized environment. Because it measures the student's ability to use clinical knowledge, diagnostic skill, and decision-making, the OSCE is thought to be more objective than traditional tests. OSCE exams have been increasingly employed in dentistry schools, particularly in the last decade, and it is crucial to investigate instructors' and dental students' experiences with this evaluation approach.